Braille Geometry Teaching Materials for Low Vision Students - Agustina, Rina; Farida, Nurul (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
Braille geometry teaching materials have media that can be touched by low vision students' sense of touch. This study aims to obtain conclusions about the feasibility and description of braille geometry teaching materials for low vision students. This research was conducted at SLBA Bina Insani Bandar Lampung and MTsLB Yaketunis Yogyakarta. The research subjects were 10 low vision students and 4 teachers. The research instrument is a feasibility questionnaire for low vision teachers and students. From the results of data analysis and discussion, it can be concluded that: (1) required mathematics learning media contained in teaching materials for low vision students, (2)Ã‚Â  braille geometry teaching materials get an average score of 91%, the appropriate category of material experts and learning, (3) braille geometry teaching materials obtained from students an average score of 86.6% included in the Very Appropriate category and from teachers with an average score of 94% included in the Very Eligible category.Bahan ajar geometri braille memiliki media yang dapat disentuh oleh indra peraba siswa low vision. Penelitian ini bertujuan untuk memperoleh kesimpulan tentang kelayakan dan gambaran bahan ajar geometri braille bagi siswa low vision. Penelitian ini dilakukan di SLBA Bina Insani Bandar Lampung dan MTsLB Yaketunis Yogyakarta. Subjek penelitian adalah 10 siswa low vision dan 4 guru. Instrumen penelitian berupa angket kelayakan guru dan siswa low vision. Dari hasil analisis data dan pembahasan dapat disimpulkan bahwa: (1) dibutuhkan media pembelajaran matematika yang terdapat pada bahan ajar bagi siswa low vision, (2) bahan ajar geometri braille memperoleh skor rata-rata 91%, kategori sesuai ahli materi dan pembelajaran, (3) bahan ajar geometri braille yang diperoleh dari siswa rata-rata skor 86,6% termasuk dalam kategori Sangat Sesuai dan dari guru dengan skor rata-rata 94% termasuk dalam kategori Sangat Layak.